Changes in Moisture Content of Corn Starch during Pneumatic Conveying - Ali, Asbi; Lamb, J (1991)
Pneumatic conveying as a means of material handling is widely used in many food processing operations. Moisture content of bulk solids is the most important factor controlling the flow properties of granular materials. This paper reports an investigation on the effect of pneumatic conveying on the moisture content of com starch powder. Changes in the moisture content of com starches during flow in the pneumatic transport conveying lines were found to be adequately described by drying theories. Fick's second law for diffusion out of spheres was used to fit the experimental drying data and the diffusion coefficients for the change in moisture content of the com starch were calculated to be in the range of 1.1 x 10-11 to 8.3 x 10-12 m2/s.